Honor bound - Bridgeman, Hallee (Love and honor ;, 2022)
"Medical missionary Cynthia Myers is trained to save lives. Captain Rick Norton of the Special Forces A-Team is ordered to take them. When Cynthia's past catches up to her, they must learn to put aside their differences to make it out alive from the treacherous jungles of a war-torn African country"--